Enhancing the optical absorption, conductivity, and nonlinear parameters of PVOH films by Bi-doping. (1st April 2021) - Ali, H Elhosiny; Yahia, I S; Algarni, H; Khairy, Yasmin
Abstract: New polymeric nanocomposite films of PVOH (polyvinyl alcohol) embedded with Bi-nanoparticles have been described by scanning electron microscopy and x-ray diffractometer. From UV-visible spectroscopy, the absorption edge shifts to the higher wavelengths direction (redshift). Tauc's model for optical bandgap transitions demonstrates that the direct and indirect values are reduced with the increase of Bi percentage in the PVOH matrix. In contrast, Urbach energy (tail bandwidth), extinction coefficient, refractive index, and optical conductivity are increased. These indicate the rise of the charge transfer among the Bi nanoparticles and the macromolecules of the matrix. Using Wemple–Di Domenico model for single-oscillator, we calculated the nonlinear optical refractive index and susceptibility. The optical limiting characteristic has been tested via a green laser source of wavelength 533 nm. The present results offer new materials for optical Cut-Off and nonlinear optical applications.